Cancer-Associated Fibroblasts Promote Proliferation of Endometrial Cancer Cells - Subramaniam, K.S.; Tham, S.T.; Mohamed, Z.; Woo, Y.L.; Adenan, N.A.M.; Chung, I. (Public Library of Science, 2013)
Endometrial cancer is the most commonly diagnosed gynecologic malignancy worldwide; yet the tumor microenvironment, especially the fibroblast cells surrounding the cancer cells, is poorly understood. We established four primary cultures of fibroblasts from human endometrial cancer tissues (cancer-associated fibroblasts, CAFs) using antibody-conjugated magnetic bead isolation. These relatively homogenous fibroblast cultures expressed fibroblast markers (CD90, vimentin and alpha-smooth muscle actin) and hormonal (estrogen and progesterone) receptors. Conditioned media collected from CAFs induced a dose-dependent proliferation of both primary cultures and cell lines of endometrial cancer in vitro (175%) when compared to non-treated cells, in contrast to those from normal endometrial fibroblast cell line (51%) (P<0.0001). These effects were not observed in fibroblast culture derived from benign endometrial hyperplasia tissues, indicating the specificity of CAFs in affecting endometrial cancer cell proliferation. To determine the mechanism underlying the differential fibroblast effects, we compared the activation of PI3K/Akt and MAPK/Erk pathways in endometrial cancer cells following treatment with normal fibroblasts- and CAFs-conditioned media. Western blot analysis showed that the expression of both phosphorylated forms of Akt and Erk were significantly down-regulated in normal fibroblasts-treated cells, but were up-regulated/maintained in CAFs-treated cells. Treatment with specific inhibitors LY294002 and U0126 reversed the CAFs-mediated cell proliferation (P<0.0001), suggesting for a role of these pathways in modulating endometrial cancer cell proliferation. Rapamycin, which targets a downstream molecule in PI3K pathway (mTOR), also suppressed CAFs-induced cell proliferation by inducing apoptosis. Cytokine profiling analysis revealed that CAFs secrete higher levels of macrophage chemoattractant protein (MCP)-1, interleukin (IL)-6, IL-8, RANTES and vascular endothelial growth factor (VEGF) than normal fibroblasts. Our data suggests that in contrast to normal fibroblasts, CAFs may exhibit a pro-tumorigenic effect in the progression of endometrial cancer, and PI3K/Akt and MAPK/Erk signaling may represent critical regulators in how endometrial cancer cells respond to their microenvironment.